2007
DOI: 10.1007/s00211-007-0106-x
|View full text |Cite
|
Sign up to set email alerts
|

Finite element approximation of spatially extended predator–prey interactions with the Holling type II functional response

Abstract: We study the numerical approximation of the solutions of a class of nonlinear reaction-diffusion systems modelling predator-prey interactions, where the local growth of prey is logistic and the predator displays the Holling type II functional response. The fully discrete scheme results from a finite element discretisation in space (with lumped mass) and a semi-implicit discretisation in time. We establish a priori estimates and error bounds for the semi discrete and fully discrete finite element approximations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…The aim of this paper is to present two stable finite-difference schemes for the numerical solution of (2) in one and two space dimensions and illustrate the simplicity of the numerical methods with short programs in MATLAB. A detailed numerical analysis of the model equations was undertaken by Garvie and Trenchea (2005b), and the current work provides the computational and implementational details needed to study the key dynamical properties of these equations. We also give the results of some numerical experiments that have ecological and numerical implications.…”
Section: Model Equationsmentioning
confidence: 99%
“…The aim of this paper is to present two stable finite-difference schemes for the numerical solution of (2) in one and two space dimensions and illustrate the simplicity of the numerical methods with short programs in MATLAB. A detailed numerical analysis of the model equations was undertaken by Garvie and Trenchea (2005b), and the current work provides the computational and implementational details needed to study the key dynamical properties of these equations. We also give the results of some numerical experiments that have ecological and numerical implications.…”
Section: Model Equationsmentioning
confidence: 99%
“…It is reported that spatial inhomogeneities like the inhomogeneous distribution of nutrients as well as interactions on spatial scales like diffusion plays an important role on the dynamics of ecological populations [2][3][4][5][6][7]. Furthermore, Holling emphasized the influence of noise in the ecological dynamics [8].…”
mentioning
confidence: 99%
“…However, this breaks up at a certain distance from the invasion front (Figure 9(c)-(f)). The existence of a propagating band of unstable waves behind an invasion front has been documented previously in numerical simulations of models for cyclic predator-prey systems [45,46,31,30,23,19,20,24]. The wavetrain band becomes narrower as ω 1 is increased, and persists as one crosses the threshold for absolute instability of the wavetrain; the behavior behind the band then changes from source-sink type (Figure 9(c),(d)) to more disordered dynamics (Figure 9(e),(f)).…”
Section: Source-sink Solutionsmentioning
confidence: 58%